Investigating Endoparasites in Captive Birds of Prey in Italy - Carolina Allievi; Sergio A. Zanzani; Fulvio Bottura; Maria Teresa Manfredi (Animals, 2024)
Birds of prey can be parasitised by several endoparasites that can coexist without clinical signs of disease or occur in conjunction with stressful events. Because the number of birds of prey kept in captivity is copiously increasing due to their use for bird control, breeding programs, exhibition and falconry, the main endoparasites of 81 apparently healthy captive birds of prey from northern Italy were investigated by examining faecal and blood samples. Faeces were analysed by a quali-quantitative technique, i.e., the FLOTAC® basic technique, employing potassium iodomercurate flotation solution, while blood smears were stained to detect haemoparasites. Risk factors were further assessed. Considering gastrointestinal parasites, an overall prevalence of 41.7% was recorded, and 50% of Accipitriformes, 43% of Falconiformes and 33.3% of Strigiformes tested positive for at least one parasite taxon. Moreover, age and diet were associated with an increased risk of infection. As for haemoparasites, a prevalence of 18.2% was evidenced, and none of the risk factors were associated with prevalence. The results of this study highlighted the importance of monitoring the endoparasites of captive birds of prey with a highly sensitive copromicroscopic technique to target medical treatments, improve housing conditions and conduct epidemiological studies aimed at wildlife conservation and management.